A Flying IoT Network to Help in Disaster Recovery - Moreira, Erick; Oliveira, Jauvane; Rosa, Paulo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
IoT platforms are considered the future of sensor networks. Its embedded nature facilitates the addition of mobility to these devices and dramatically broadens the possibility of using such systems. Especially when shipped on aerial vehicles, those networks can be quickly utilized to assess crises. During disaster recovery operations, instant communication is of the essence for the coordination of activities. However, those scenarios commonly are deprived of good communication infrastructure. This work proposes a system capable of deploying an instant network mounted on UAVs that connects all interested parties through an IPv6 mesh network made of IoT devices. The experiments showed that a small set of 50 UAVs equipped with a 50-meter range communication device is capable of connecting up to 24 elements spread over an area of 13,000 square meters. For a set of 150 UAVs, it was possible to serve an average of 68 agents in an area of 25,600 square meters.